2021
DOI: 10.1101/2021.11.05.467432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outer Membrane Vesicles from the gut microbiome contribute to tumor immunity by eliciting cross-reactive T cells

Abstract: The gut microbiome plays a key role in cancer immunity. One proposed mechanism is through the elicitation of T cells, which incidentally recognize neo-epitopes arising from cancer mutations (“molecular mimicry (MM)” hypothesis). To support MM, Escherichia coli Nissle was engineered with the SIINFEKL epitope (OVA) and orally administered to C57BL/6 mice. The treatment elicited OVA-specific CD8+ T cells in the lamina propria and inhibited the growth of OVA-B16F10 tumors. Importantly, the administration of Outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Moreover, Cheng et al chemically associated tumor T cell epitopes to E. coli OMVs and showed that such OMVs protected mice against the challenge with tumors expressing such epitopes 22 . Finally, OMVs expressing specific tumor neo-epitopes either released by intestinal commensal bacteria or administered by oral gavage were shown to protect mice from tumor challenge 18,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Cheng et al chemically associated tumor T cell epitopes to E. coli OMVs and showed that such OMVs protected mice against the challenge with tumors expressing such epitopes 22 . Finally, OMVs expressing specific tumor neo-epitopes either released by intestinal commensal bacteria or administered by oral gavage were shown to protect mice from tumor challenge 18,23 .…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 7, 2023. ; https://doi.org/10.1101/2023.04.07.536036 doi: bioRxiv preprint peptide epitopes elicit anti-tumor immunity [15][16][17][18] . This offers the opportunity to test whether the inclusion of tumor-specific epitopes to the ISV formulation further potentiates the efficacy of ISV.…”
Section: Introductionmentioning
confidence: 99%